Corporate Criminal Liability in the Social Security Organizing Agency Law - Ningsih, Dwi Wachidiyah; Suyanto, Suyanto (IHSA Institute, 2025)
Employees who should be protected and given social security are often not provided by the corporation, but employees still have to work without any legal protection. This research aims to find out the form of corporate criminal liability in the Social Security Organizing Agency Law and the mechanism for applying sanctions in that law. This research uses normative legal research methods by examining laws and regulations, especially UUBPJS and other library materials related to Social Security Organizing Agency Law issues. The results showed that the Social Security Administration Law No.24 of 2011 does not regulate corporate criminal liability in matters of membership obligations, but corporations can be held criminally responsible if the collection of contributions does not run following the staging that has been determined for BPJS participants